2022
DOI: 10.1021/acsapm.1c01870
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Oxidative and pH Dual-Responsive Photonic Crystals Based on Sulfide-Containing Block Copolymers

Abstract: Photonic crystals (PCs) derived from responsive polymers exhibit adjustable photonic band gaps under external stimuli, and they have abundant applications in different fields. Herein, oxidative and pH dual-responsive copolymers were synthesized using reversible addition–fragmentation chain transfer (RAFT) polymerization with a functional monomer of combined phenyl vinyl sulfide (PVS) and N,N′-(dimethylamino) ethyl acrylate (DMAEA). The oxidatively responsive PVS segment generated copolymers with a refractive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…SEM, water contact angle, reflectance spectroscopy and GPC (DMF) measurements were carried out using the instruments and test methods described in ref. 38. The molecular weight and molecular weight distribution of the polymer after oxidation were measured using a GPC (Waters 6250) (RI detector) equipped with a PL aquagel-OHMIXED-M column at 25 °C calibrated with PEG standards with a flow rate of 1.0 mL min −1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SEM, water contact angle, reflectance spectroscopy and GPC (DMF) measurements were carried out using the instruments and test methods described in ref. 38. The molecular weight and molecular weight distribution of the polymer after oxidation were measured using a GPC (Waters 6250) (RI detector) equipped with a PL aquagel-OHMIXED-M column at 25 °C calibrated with PEG standards with a flow rate of 1.0 mL min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Such a PC showed multiresponsive behavior derived from oxidative changes in the ‘ n ’ value of PVS and from pH changes in the ‘ d ’ value of DMAEA. 38 The results indicated that the obtained PC showed multiresponsive behavior with both redox and pH stimulation. However, due to the contradiction between the DMAEA unit content and the overall refractive index of the polymer, only the block copolymer exhibited the dual response.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Organosulfur compounds constitute a significant part of organic synthesis 1 because they are useful in medicinal chemistry, 2 materials science, 3 and natural product syntheses. 4 Thioethers (sulfides) have found attractive applications in the pharma industry.…”
Section: Introductionmentioning
confidence: 99%
“…By decreasing the BCP film thickness to scale consistently with the natural period of the polymer ( L 0 ), it is possible to generate a range of structures. These morphologies can be utilized in several industrial applications, such as lithographic masks, membranes, and photonics . Moreover, the BCP can act as an engineered template for inclusion of inorganic species. , The confinement of a polymer in a thin film (typically <100 nm) changes its behavior compared to the bulk counterpart: thin films are subjected to interactions with the interfaces, for example, substrate and air.…”
Section: Introductionmentioning
confidence: 99%